Thermal and ablation properties of a high-entropy metal diboride: (Hf0.2Zr0.2Ti0.2Ta0.2Nb0.2)B2. Issue 11 (September 2023) - Hoque, Md Shafkat Bin; Milich, Milena; Akhanda, Md Sabbir; Shivakumar, Sashank; Hoglund, Eric R.; Staicu, Dragos; Qin, Mingde; Quiambao-Tomko, Kathleen F.; Tomko, John A.; Braun, Jeffrey L.; Gild, Joshua; Olson, David H.; et al.
Abstract: The fabrication of high-entropy ceramics has recently expanded the pool of ultra-high temperature ceramics (UHTCs). To properly assess the suitability of these new types of ceramics for advanced aerospace applications, it is of vital interest to extend the characterizations beyond ambient conditions. Here, we have studied the thermal and ablation properties of a high-entropy diboride (HEB): (Hf0.2 Zr0.2 Ti0.2 Ta0.2 Nb0.2 )B 2 . The thermal conductivity of the HEB increases as a function of temperature and becomes comparable to that of other UHTCs at high temperatures. The electron dominated thermal conductivity of HEB is also nearly isotropic along different crystallographic orientations. The temperature-dependent volumetric heat capacity of HEB is measured and found to remain in agreement with that of ZrB 2 . Additionally, both material systems possess nearly the same ablation resistance. The multitudes of characterizations performed in this study establishes the suitability of HEB for high thermal load applications in extreme environments.